Prevalence, characteristics, and acute care utilization of disabled older adults with an absence of help for activities of daily living: Findings from a nationally representative survey. (November 2016) - Wang, Hui-Hsuan; Shyu, Yea-Ing Lotus; Chang, Hsing-Yi; Bai, Yuh-Bin; Stanaway, Fiona; Lin, Jen-Der; Li, Chia-Lin
Highlights: No help for ADL was reported in 16.6% of disabled older adults. Disabled older adults reporting an absence of help were more likely to be female. No help for ADL disability was associated with a greater burden of acute care utilization than those without disability. Abstract: Objective: The aim of this study was to investigate the prevalence, characteristics, and acute care utilization of community dwelling disabled older adults with an absence of help for activities of daily living (ADL). Methods: We analyzed cross-sectional data from a nationally representative sample of people aged 65 years and over (n = 2904) participating in the 2009 National Health Interview Survey in Taiwan. Disability was defined as self-reporting a lot of difficulty or complete inability to carry out one or more ADL tasks. Participants with disability were asked whether they received help in the form of personal assistance or assistive devices to complete ADL tasks, with a yes response indicating the presence of help and a no response indicating the absence of help. Hospitalization and emergency department visits was assessed as a dichotomous variable (any or none), respectively. Results: An absence of available help for ADL disability was reported in 16.6% of disabled older adults. Disabled older adults reporting an absence of help were more likely to be female. After adjustment for other factors, compared to older adults without disability, older adults with disability not receiving help for ADL tasks were highly related to hospitalization (OR = 4.57; 95%CI = [1.51–13.82]) and emergency department visits (OR = 3.52; 95%CI = [1.15–10.76]) during the past year, respectively. Conclusions: We found that there is high prevalence of absence of help to perform ADL tasks in older adults with disability, and that this absence of help for ADL disability is associated with a greater burden of acute care utilization than those without disability.